A BRIEF REVIEW OF SIYASAH SYAR'IYYAH ON THE SUPERVISION OF PUBLIC SERVICES AT THE BULUKUMBA REGENCY SAMSAT OFFICE - Azzer Arifuddin (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to discuss a brief review of Siyasah Syar'iyyah on public service supervision at the Bulukumba Regency Samsat office. This study is qualitative in nature. The research design is field research. The results of this study show that internal supervision is carried out routinely as a form of our commitment to maintaining integrity and ensuring that every procedure runs in accordance with applicable regulations. Meanwhile, external supervision is carried out through public reports, among other things. In addition, transparency is a form of accountability to the public. It is implemented by the Bulukumba Samsat UPTB through every transaction accompanied by official proof of payment in accordance with applicable regulations. In this way, the tax payment process can take place in a fair, professional, and accountable manner. Furthermore, one of the efforts that is considered a form of transparency is that the Bulukumba Samsat UPTB presents a list of official fees and service procedures openly through various media, such as bulletin boards, websites, and social media platforms. The purpose of this step is so that the public can easily obtain information, thereby avoiding illegal practices and illegal levies. This reality demonstrates its benefits. It is an indicator of alignment with Siyasah Syar'iyyah.